Antibacterial potential of Croatian honey against antibiotic resistant pathogenic bacteria - Ivana Gobin; Crnković Goranka; Maja Magdalenić; Gabrijela Begić; Ana Babić; Dražen Lušić; Darinka Vučković (Medicinski glasnik, 2018)
Aim: To determine antimicrobial activity of honey against clinical bacterial strains and their respective reference strains. Methods: Twelve samples of Croatian honey from various botanical origin were evaluated for their antimicrobial activity against four clinical antibiotic resistant pathogens and their respective reference strains: Staphylococcus aureus, Acinetobacter baumannii, Pseudomonas aeruginosa and Escherichia coli. Antibacterial susceptibility was checked out by using broth microdilution method and interpreted according to the European Committee for Antimicrobial Susceptibility Testing (EUCAST) recommendations. Results: Significant differences in the antibacterial activity of tested honey samples were noticed. Fir honeydew honey and Mint honey showed the best antibacterial potential, while the Locust tree honey, Rapeseed honey and Spring pasture honey expressed the weakest antimicrobial activity. Conclusion: Croatian honey, prominently honeydew honey, has the potential to become an important additive to therapeutic techniques available to a medical practitioner against resistant pathogens, but the exact mechanisms of its activity should be investigated further.
Keywords: antimicrobial activity; honeydew; pathogens; therapy